The potential of mealworm (Tenebrio molitor) and field cricket (Gryllus assimilis) AS alternative nutrient sources in ruminant feed production - Husna Fasihah; Hamdan Ahmad; Shehu Ibrahim Kura; Intan Haslina Ishak (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since the world population reaches nine billion by 2050, both humans and animals may experience further malnourishment and starvation. It is crucial to comprehend the current state of food waste and reuse. The food wastes were used in this study as media in rearing process of two type of insects (mealworm and cricket). The study was carried out to evaluate the potential of mealworm (Tenebrio molitor) and field cricket (Gryllus assimilis) as a supplement diet to produce high-quality feed for ruminant animals in Malaysia. Rearingprocedures were carried out using two different media viz; conventional basic diet (CBD) and alternative feed (AF) as insects feed. The nutritional elements (i.e., dry matter, crude protein, metabolizable energy, ether extract, crude fibre, acid detergent fibre, organic matter digestibility and total digestible nutrient) in four insect stages (larvae and pupae of mealworm, nymphs and adults of cricket) were assessed proximately using standard techniques which is the Kjeldhal method for protein, Soxhlet apparatus for crude fat analysis, crude fibre, and van soest acid detergent fibre procedures. The results revealed that, nutritional elements in the insect stages of development in two different diets were very significant and proved mealworm that consume alternative feed from food waste is the best feed. Mealworm is the best group because of the high main nutritional element was observed in CP and EE (42.90±1.17 and 32.96±0.84, respectively). While, the low in indigestible nutrient i.e., CF and ADF with values of 4.14±0.31 and 18.32±0.56. However, these values significantly differed (P<0.05) from most of the groups. Therefore, the findings suggested that these insects contain a promising level of the required nutrient compositions particularly mealworm which highly demonstrated potential ingredients to be formulated in high quality animal feed.